Effektivare hantering av foderspannmål : en fallstudie - Thuresson, Henrik (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The purpose with this work was to investigate some alternatives for an effective handling with grain, to find the most economic alternative. It is not common that moisture content is below 14% when harvesting grain in Sweden. To store the grain safe it has to be preserved in some way. I have described some of the most common systems for preserving grain in this paper. I have used the systems as a basis when I made calculations in handling the grain for a company. I have chosen a company placed in south of Sweden. The productions are crop farming and pork. In one of the sites in the company there are pigs and grain drier/feed preparation. All feed preparation for the pigs are made at this site. There are pigs in another two sites. Grain is stored in two other sites situated 2 km and 1 km away from the drier. Today the company dries and store 1800 tons of grain. In this paper I have investigated the cost of some parts of the handling with grain in the company today. To get prices for new equipment I have been in contact with sellers. I have calculated alternatives that are possible for this company. The result shows that an expansion for storage at the site of the existing drier is the most profitable. If the capacity of the drier is fully used, it is more profitable to build a bin drier at one of the other stables with pigs. The airtight storage is a big investment and because of that, the system can not compete with the others.